1992
DOI: 10.1095/biolreprod46.2.265
|View full text |Cite
|
Sign up to set email alerts
|

Biological Actions of Monoclonat Luteinizing Hormone/Human Chorionic Gonadotropin Receptor Antibodies1

Abstract: Several recent studies have elucidated the structure of the mammalian LH/hCG receptor; as reported in the present work, we have developed a series of monoclonal antibodies (mAbs) against the rat ovarian LH/hCG receptor using highly purified receptor as immunogen and by screening hybridomas with purified LH/hCG receptors. The mAbs were able to specifically immunoprecipitate LH/hCG receptors from solubilized preparations of rat ovarian membranes as well as from partially purified preparations. Western blotting w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 37 publications
2
30
0
Order By: Relevance
“…The LH receptor monoclonal antibody P1B4 was a gift from Dr J Wimalasena (Department of Obstetrics and Gynecology, University of Tennesse, Knoxville, TN, USA). The antibody was raised against purified rat LH receptors, as described by Indrapichate et al (16), and has been shown to bind to LH receptors in the human.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…The LH receptor monoclonal antibody P1B4 was a gift from Dr J Wimalasena (Department of Obstetrics and Gynecology, University of Tennesse, Knoxville, TN, USA). The antibody was raised against purified rat LH receptors, as described by Indrapichate et al (16), and has been shown to bind to LH receptors in the human.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Samples were fixed in 0.5% paraformaldehyde, and hC'G receptors were visualized with the anti-LHR monoclonal antibody, PIB4. of the IgM class [30], fol lowed by fluorescein-conjugated rabbit anti-mouse IgM (Organon Teknica/Cappel). The percent capping was determined by counting a minimum of 100 cells, which were considered to have capped if the fluores cent surface label was concentrated in a polar area comprising half or less of the cell.…”
Section: Induction and Visualization Ofhcg Receptormentioning
confidence: 99%
“…but exhibits only minimal cross-reactivity with the FSH receptor [30. 40], The available data show that the epitope is extracellular and presumably represents a well-conserved and LH/hCG-specific region of the N-terminal receptor domain [3], Earlier work demonstrated that the P1B4 antibody partially inhibits hCG binding and hCG-stimulated progesterone production in porcine granulosa cells [30]. Our immunofluorescence studies with the murine MA-10 cells did not directly address this issue, but the data suggest that the monoclonal antibody will recognize both the unoccupied and the hCG-bound forms of the receptor.…”
Section: Ma-10 Cells Exhibit a Uniform Surface Dis Tribution Of Lhr Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Porcine granulosa cells were isolated from medium sized antral follicles (4-6 mm) as described previously, 28,29 and maintained as the human epithelial SC above, including propagation, freezing and thawing.…”
mentioning
confidence: 99%